Novel poly(lactic acid)–poly(ethylene oxide) chain‐linked copolymer and its application in nano‐encapsulation. (5th February 2014) - Pavelkova, Alena; Kucharczyk, Pavel; Stloukal, Petr; Koutny, Marek; Sedlarik, Vladimir
<x xml:space="preserve">Abstract</x> The work presented here investigates the synthesis of poly(lactic acid)–poly(ethylene oxide) diisocyanate chain‐linked copolymer, and its application in the nano‐encapsulation of bioactive compounds. Study was conducted on the effect of the type of chain‐linking agent, along with molecular weight, thermal properties and hydrophilic/hydrophobic behavior, through the methods of gel permeation chromatography, Fourier transform infrared spectroscopy–attenuated total reflectance, differential scanning calorimetry, light scattering, water uptake experimentation, and water contact angle measurements. Nanoparticle formation was performed via a single solvent evaporation process, and the particles obtained were characterized by dynamic light scattering and scanning electron microscopy. Results show the significantly enhanced molecular weight of the final product after the chain‐linking reaction (up to 300, 000 g/mol), as well as the non‐linear nature of the sample due to broad polydispersity, ranging from 4–13. The final products exhibited glass transition temperatures of between 30 and 44 °C, while their crystalline quality was either significantly suppressed or a completely amorphous attribute was observed. Nanoparticles in the range of 300 nm that contained metazachlor were successfully prepared, and their releasing behavior exhibited first order release kinetics. A slower rate of release was observed in samples containing 4, 4′‐methylenebis(phenyl isocyanate) as a chain‐linker. Copyright © 2014 John Wiley & Sons, Ltd.